Singhiella melanolepis, a new species of whitefly (Hemiptera: Aleyrodidae) from Taiwan with remarks on the genus Singhiella Sampson - Chen, Young-Fa; Ko, Chiun-Cheng (Zootaxa, 2007)
The adult male, female and puparium of Singhiella melanolepis sp. nov. are described from Melanolepis multiglandulosa (Euphorbiaceae), together with scanning electron micrographs and figures. Comparisons are made between the puparium of this species and that of Singhiella elaeagni (Takahashi 1935), and remarks are provided on the genus Singhiella Sampson. After consideration of the diversity in adult structure among the species of Singhiella, it is suggested that this genus may be defined unsatisfactorily, and that more importance should be placed on adult morphology in whitefly taxonomy.